Follow-up Analysis of Serum TNF-Related Apoptosis-Inducing Ligand Protein and mRNA Expression in Peripheral Blood Mononuclear Cells from Patients with Ischemic Stroke - Tufekci, Kemal Ugur; Vurgun, Ufuk; Yigitaslan, Onur; Keskinoglu, Pembe; Yaka, Erdem; Kutluk, Kursad; Genc, Sermin (Frontiers in Neurology, 2018)
Tumor Necrosis Factor (TNF)-related apoptosis inducing ligand (TRAIL), which is TNF receptor superfamily member, contributes to several diseases pathogenesis. The aim of this research was to investigate the relevance of serum TRAIL protein levels and mRNA expression in peripheral blood mononuclear cells (PBMC) of patients with stroke through six months follow-up. We enrolled patients with first-ever acute ischemic stroke (n=95) and healthy controls (n=95) in this study. Follow-up blood samples were collected from patients at day 7, 28, and 180 after the onset. The stroke severity was evaluated by National Institutes of Health Stroke Scale (NIHSS) score. TRAIL protein levels were quantified by using ELISA kits and TRAIL mRNA expression by quantitative real-time PCR. Our study showed that stroke patients have statistically significant lower levels of serum TRAIL protein (p<0.0001) and elevated TRAIL mRNA expression (p<0.0001) in peripheral blood mononuclear cells at the disease onset. Our follow-up study revealed that TRAIL protein levels were downregulated while mRNA expression levels were increased in later periods. Overall, our findings suggest that serum TRAIL levels and mRNA expression in PBMC could reliably serve as a predictor of stroke outcome. Additionally, our study supports that TRAIL plays a role in pathogenesis and progression of ischemic stroke.